The association between chronotype and suicidality among students of the medicine and psychology faculties – the mediating role of general mental health indices. (3rd April 2021) - Mokros, Łukasz; Nowakowska-Domagała, Katarzyna; Koprowicz, Jacek; Witusik, Andrzej; Pietras, Tadeusz
ABSTRACT: The aim of the present study was to evaluate whether anxiety and insomnia symptoms, somatic symptoms, and social dysfunction mediate the link between chronotype and suicidality, as depressive symptoms are known to do, among students of the faculties of Medicine and Psychology. Data from a total of 289 students were eligible for the analysis. The students completed the Suicide Behaviors Questionnaire – Revised, Composite Scale of Morningness, General Health Questionnaire. Single-predictor linear regression models were created to predict suicidality, with a subsequent mediation analysis. A preference toward eveningness was associated with an increase in suicidality Somatic symptoms, anxiety/insomnia, and depressive symptoms fully mediated the relationship between chronotype and suicidality. Depressive symptoms were found to present the strongest effect size of mediation. Social dysfunction was associated with both eveningness and suicidality, but did not play a mediating role. There might be a need to evaluate nonpsychotic mental health indices other than depressive symptoms when assessing the link between suicidality and chronotype among students of the faculties of Medicine and Psychology.